PERILAKU KONSUMEN DALAM MEMILIH PERUMAHAN PADA PERUMAHAN CIPTA LARAS BULUSULUR WONOGIRI - Murwanti, Sri (Benefit: Jurnal Manajemen dan Bisnis, 2009)
This study aims to analyze the relationship between consumer characteristics andproduct attributes. Dimensions of consumer characteristics, are age, education, occupation,and income consumers. While, the dimention of product atribute are price, design, facility andlocation. This researchâs setting is in the property industry. The research uses chi-square as atool of analysis. The results show that there is a relationship between consumerâs characteristicsandÂ productÂ attribute.Â EducationÂ levelÂ hasÂ theÂ highestimpactÂ to productÂ attribute.